Rehabilitation of urban areas of precarious settlements (favelas) using GIS - Gerson José de Mattos Freire (Disegnare con, 2013)
To maximize their reach and effectiveness, adoption of public policies for urban planning must be supported by techniques that allow the seizure and analysis of data relating to the territory where they apply these policies. The article exposes the Vila Viva program, established by the City Administration of Belo Horizonte, Brazil, proposing to integrate into the urban tissue consolidated informal settlements (a.k.a. slums) and that had their environmental studies supported intensively by GIS techniques. By combining information from different sources, these techniques enabled not only the diagnosis of the slums, but also of the formal urban environments where they are located and which the policy seeks to integrate them into. The priorities for action were set up by combining technical criteria calibrated by the vision of a government policy that for eight years have been object of projects and works by the municipality. The paper compares the scenarios obtained in the original environmental study and the current reality, evaluating the results achieved in the proposed integration of slums and their effects on environmental quality.